Evaluation of Hepatitis B screening and reactivation in patients receiving rituximab containing chemotherapy: A single‐centre study. Issue 10 (9th August 2021) - Bozkurt, Ilkay; Ozturk Cerik, Hatun; Kir, Seher; Ustaoglu, Muge; Turgut, Mehmet; Esen, Saban
Abstract: Aims: Hepatitis B virus (HBV) infection is a worldwide distributing viral disease. Hepatitis caused by HBV reactivation may progress to chronic illness and associated with increased risk of hepatic failure and hepatocellular cancer. Rituximab (RTX) is an immunosuppressive agent, is particularly used in the treatment of non‐Hodgkin's Lymphoma. Patients have significant risk for HBV reactivation following chemotherapy with a RTX‐containing regimen. This study aimed to determine the HBV screening manner and reactivation rates in patients with haematological neoplasm following chemotherapy including Rituximab. Methods: This is a single‐centered retrospective cohort study. A total of 331 adults with haematological disorders who received chemotherapy regimen including RTX between years of 2006 and 2016 were enrolled. Patients who experienced reactivation were evaluated. Results: Only 130 of 331 patients were screened appropriately for HBV infection for 10‐year period. We found 18 patients were Hepatitis B surface antigen (HBsAg) (+) and 16 (88.8%) of them received antiviral prophylaxis. Among screened patients, 27 were HBsAg (−)/AntiHBc (+) and only 10 (37%) of them received HBV prophylaxis. In total, nine patients experienced reactivation, six were from screened and three were from unscreened group. Conclusion: Incomplete screening and inappropriate prophylaxis may result in HBV reactivation in patients under RTX‐based chemotherapy and related complications such as death.